Environmental education and digital solutions: An analysis of the Lebanese context’s existing and possible digital actions - Khalifé, Mona; Chaker, Rawad; Gasparovic, Slaven (Frontiers in Education, 2022)
One of the main purposes of environmental education is to tackle the youth belief system and raise specific concerns linked to ecology and sustainability. Nonetheless, the educational approach to ecological concerns is partly about the methods used to reach effective results. The advancement of technologies and the rapid spread of social media have accelerated the use of online means of communication. While technology and digital tools have proven effective for educational purposes, it becomes necessary to examine the relationship between technology and environmental education, particularly in the Lebanese context. This position paper provides a review of studies on education, the environment, and digital tools, more specifically, studies conducted in Lebanon. It particularly focuses on the engagement of educational institutions and social incentives to raise environmental awareness and develop ecological behaviors in Lebanon. The results of this study will help stakeholders and researchers for future implementation of digital solutions in the Lebanese context toward a greener agenda.